Advances in the use of structural and diffusion magnetic resonance imaging for characterizing SCD and MCI due to Alzheimer’s disease - Yang, Hao; Dong, Cheng; Cai, Ying; Zhao, Mingming; Liu, Junfang; Bian, Shizhu; Ding, Xiaohan (Frontiers in Neuroscience, 2025)
Alzheimer’s disease (AD) has become a great concern for society in general and clinicians specifically because of its high morbidity, relative lack of awareness of its characteristics, and low diagnosis and treatment rates. Worldwide, there is a lack of effective treatments for slowing the progression of AD in clinical practice. Thus, the management of patients in the preclinical phase of AD (PPAD) has been identified to be highly important for addressing this concern. PPAD is considered a preclinical manifestation of the early stages of AD and includes subjective cognitive decline (SCD) and mild cognitive impairment (MCI). Developments in magnetic resonance imaging (MRI) technology have led to its demonstration of great potential in the early identification and progression monitoring of PPAD. Thus, in this review, we summarized the concepts, principles and applications of structural and diffusion MRI in the identification of PPAD to provide potential imaging markers that can be used by clinicians in clinical practice.